2015
DOI: 10.4314/njbas.v23i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Vitamin E on Nicotine Induced Reproductive Toxicity in Male Rats

Abstract: The current study assessed the protective role of vitamin E in alleviating the detrimental effect of nicotine on reproductive functions in male rats. Twenty four male albino rats were divided into four groups of six rats. Control group was treated orally with 1.1 ml/kg body weight normal saline, nicotine treated group received 1.0 mg/kg body weight of nicotine, vitamin E treated group received 100 mg/kg body weight of vitamin E while nicotine plus vitamin E treated group received 1.0 mg/kg body weight of nicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Low sperm counts are associated with reduced fertility because spermatozoa from ejaculates with low counts often contain many spermatozoa with poor motility and sperm debris. Studies have shown that supplementation of vitamin E in nicotine‐treated rats improves both sperm quality and quantity (Mahanem, Nor‐Asmaniza, Phang, & Muhammad, ; Oyeyemi, Shittu, Kolawole, Ubanecheand, & Akinola, ).…”
Section: Discussionmentioning
confidence: 99%
“…Low sperm counts are associated with reduced fertility because spermatozoa from ejaculates with low counts often contain many spermatozoa with poor motility and sperm debris. Studies have shown that supplementation of vitamin E in nicotine‐treated rats improves both sperm quality and quantity (Mahanem, Nor‐Asmaniza, Phang, & Muhammad, ; Oyeyemi, Shittu, Kolawole, Ubanecheand, & Akinola, ).…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that administration of Vitamin E alone may be insufficient in the management or treatment of reproductive toxicity in CP-exposed subjects. Apparently, in animal model there seem to be a standard reference of 100 mg/kg of vitamin E administration in the treatment of drug- or chemically-induced reproductive toxicity [13] , [14] , [15] . This study, however, showed that this dose-reference did not prove much of a standard as shown in some of the reproductive indices such as FSH and lipid peroxidation (TBARS) when compared with both the extract-treated groups and the control.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E, a group of compounds comprising both tocotrienols and tocopherols, is a lipid-soluble antioxidant that protects cell membranes from oxidation by reacting with lipid radicals that are produced in the lipid peroxidation chain reaction as well as expresses its antioxidant functions in the glutathione peroxidase pathway [8] , [9] , [10] . Its most biologically active form is alpha tocopherol [8] , [11] and is apparently a conventional drug used in the amelioration of xenobiotics-induced reproductive toxicity in animal models [12] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable oils, eggs, butter, wholemeal cereals, fruits, green leafy vegetables and seafood are good sources of Vit E. The vitamin is involved in cell signaling, expression of gene control, immune regulation and other metabolic processes (Traber et al 2006). It has also been reported to protect genetic materials in the spermatozoa, as well as improved fertility (Kalthur et al 2011;Oyeyemi et al 2015).…”
Section: Introductionmentioning
confidence: 99%